Spectrum of Myeloma with Varied Presentations at a Tertiary Care Centre - Sabiha Tasneem Shaik; Chaitanya Latha Sappidi; Gudeli Vahini (Journal of Medical Sciences and Health)
Introduction: Multiple myeloma is a disorder caused by neoplastic proliferation of malignant plasma cells. It comprises about 15% of all hematologic malignancies and contributes to 1% of cancer deaths. Its incidence is higher in males with a peak age of incidence of 65-70 years. Objective: To study the incidence of multiple myeloma and to correlate with clinical, Biochemical, Radiological, hematological and Bone Marrow findings. Methods: This was a record based retrospective study conducted over a period of 1 year in Alluri sitaramar aju Academy of Medical sciences. Patients admitted in medical wards with features of anemia, bone pains, lytic bone lesions and renal failure were included. Hematological investigations such as Hemoglobin (Hb) estimation, total and differential cell counts, erythrocyte sedimentation rate (ESR), platelet count, peripheral blood smear, bone marrow examination was done. Urine examined for Bence Jones protein. Serum protein electrophoresis to detect M band, serum beta microglobulins, serum albumin was done in all cases. Radiological investigations included skeletal survey, imaging studies like PET -CT, MRI were performed where indicated. Evaluation was done based on Revised international myeloma working group 2021. Results: This study includes 30 cases which were diagnosed in the one-year study period with majority people in seventh decade, age ranging from 38-72. There is male preponderance. Fever, fatigue, and anemia are seen in 97% cases (29/30), Bone pains seen in 83% cases (25/30), Lytic bone lesions with fractures seen in 67% cases (20/30), Renal failure on dialysis seen in 27% cases (8/30). Bence jones proteins seen in 13% cases (4/30), serum electrophoresis showing decrease in albumin levels seen in 20% cases (6/30), increased beta 2 micro globulin in 23% cases, serum LDH elevated in 16% cases, serum calcium elevated in 60% cases (18/30). Conclusion: Among 30 cases, most of these cases presented with varied clinical, Hematological, and radiological presentations. So, patients in old age with such varied presentations should be worked up to rule out multiple myeloma.